Penyelenggaraan Otonomi Daerah Bidang Pendidikan Berdasarkan Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Danetta Leoni Andrea (Kyadiren, 2020)
The existence of regional autonomy creates an authority relationship between the central government and the regions. In this case, the relationship between the center and the regions discussed by the author more focused on the relationship of educational authority. Given that the national education system has an important role in educating the Indonesian nation. In addition, during globalization, education is needed that is able to produce qualified human resources so that they can compete in the international world. The relationship between the central government and the regions can be seen from regional autonomy giving birth to the relationship between the central government and the regions, one of which is the relationship of educational authority which includes education management, curriculum, accreditation, educators and education staff, education licensing, and language and literature